2008
DOI: 10.1038/sc.2008.120
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity is related to lower levels of pain, fatigue and depression in individuals with spinal-cord injury: a correlational study

Abstract: Study design: This was a prospective cross-sectional study for people with chronic spinal cord injury (SCI). Objectives: To (1) evaluate the intensity level and nature of physical activity in community-dwelling individuals living with SCI, and (2) explore the relation between descriptive individual variables (for example, lesion level), secondary complications and participation in physical activity. Setting: Urban community setting. Methods: A total of 49 subjects with SCI who used a manual wheelchair for prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
2
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 23 publications
5
79
2
1
Order By: Relevance
“…20 Our finding is consistent with that of a previous study that showed that less exercise was related to more fatigue 5 and heavy intensity activity was related to lower fatigue in persons with chronic SCI. 12 However, we found no relationship between fatigue and physical behavior in our study. Therefore, we could not confirm the fatigue, physical fitness and physical behavior cycle hypothesis proposed by Durstine et al 6 However, our physical behavior measurement was limited to outcomes on postures, wheeled physical activity and mean motility of trunk and arms.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…20 Our finding is consistent with that of a previous study that showed that less exercise was related to more fatigue 5 and heavy intensity activity was related to lower fatigue in persons with chronic SCI. 12 However, we found no relationship between fatigue and physical behavior in our study. Therefore, we could not confirm the fatigue, physical fitness and physical behavior cycle hypothesis proposed by Durstine et al 6 However, our physical behavior measurement was limited to outcomes on postures, wheeled physical activity and mean motility of trunk and arms.…”
Section: Discussioncontrasting
confidence: 54%
“…In persons with SCI in the chronic phase, fatigue has been shown to relate to age 10 and lesion characteristics. 4 With regard to physical factors, being overweight has been found to negatively impact fatigue, 11 and physical activity that requires a lot of physical effort 12 is related to less fatigue in persons with SCI in the chronic phase.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although there are few estimates of the prevalence of fatigue in SCI, there is evidence to suggest that this is a common concern. [1][2][3][4][5][6] In fact, a study of an outpatient sample of individuals with SCI reported that 57% experienced fatigue, which interfered with daily function. 7 The experience of fatigue was found to be exacerbated by other factors (for example, spasticity, completeness of injury, medication use).…”
Section: Introductionmentioning
confidence: 99%
“…10 This paindepression-fatigue triad is commonly reported clinically and in the literature as a complex multifactorial relationship that impacts function for individuals after SCI 11 and has been demonstrated to be associated with factors such as physical activity. 5 Pain 8 and depression 12 have each been shown to be associated with participation in community activities, an outcome recognized for its relationship to overall health 13 and quality of life. 14 The relationships between factors are complex, and, it is clear it would be difficult to consider the association between participation and a single factor (that is, fatigue), without considering the influence of related factors.…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, pain has been shown to directly interfere with sensorimotor functions, such as the capacity to learn locomotor 9 and upper limb motor 10 tasks. As such, simultaneous treatment of motor functions and pain would be preferred over conventional treatment, that is suboptimal as evidenced by the high prevalence of chronic pain.…”
Section: Introductionmentioning
confidence: 99%